Factors affecting students' motivation in learning English listening skills at An Lao High School - Nguyễn, Thị Tuyến (University of Languages and International Studies, 2017)
This thesis studies factors affecting students' motivation in Learning English Listening skills at An Lao High School. The tools for data collecting were questionnaire and interview. Concerning the current results of the research were not satisfying.